Solanum tuberosum L. Sp. Pl. - OVCHINNIKOVA, ANNA; KRYLOVA, EKATERINA; GAVRILENKO, TATJANA; SMEKALOVA, TAMARA; ZHUK, MIKHAIL; KNAPP, SANDRA; SPOONER, DAVID M. (Zenodo, 2011)
4. Solanum tuberosum L. Sp. Pl. 185. 1753 . Battata tuberosa Hill, Hort. Kew. 148. 1768, Lycopersicon tuberosum (L.) Mill., Gard. Dict. ed. 8, no. 7. 1768, Solanum esculentum Neck., Delic. Gallo-Belg. 1: 119. 1768, Solanum tuberosum L. var. vulgare Hook. f., Bot. Antarct. Voy. I. (Fl. Antarct.) 2: 329. 1846, Solanum tuberosum L. var. cultum A.DC. Arch. Sci. Phys. Nat. ser. 3, 15: 437. 1886, Solanum tuberosum L. var.? vulgare Macloskie, Rep. Princeton Univ. Exped. Patagonia 8: 707. 1905, Solanum cultum (A.DC.) Berthault, Recherc. Bot. var. Cult. Solanum tuberosum , etc. 127, 128. 1911. Type: cultivated in Uppsala, Anon. (lectotype, LINN! [LINN 248.12, BH neg. 6799], designated by Hawkes, 1956b: 106). [C] Figure 4. Solanum sinense Blanco, Fl. Filip. ed. 1: 137. 1837. Type: Philippines. Sin. loc. cultivated, F. Blanco s.n. (no specimens found). [C]. Solanum tuberosum L. var. leonhardianum Alef., Landw. Fl. 137. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. melanoceras Alef., Landw. Fl. 137. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 29, designated here). [C]. Solanum tuberosum L. var. californicum Alef., Landw. Fl. 138. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. erythroceras Alef., Landw. Fl. 138. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. holsaticum Alef., Landw. Fl. 138. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. cucumerinum Alef., Landw. Fl. 139. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. julianum Alef., Landw. Fl. 139. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. menapianum Alef., Landw. Fl. 139. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. platyceras Alef., ...